Public Relations Strategy in Improving Reputation of Crystal Hotel - Lena, Pratika Martha; Lusianawati, Hayu (Eastasouth Institute, 2024)
The hospitality industry, including Crystal Hotel, faced significant challenges during the COVID-19 pandemic. Public Relations (PR) strategies play a crucial role in maintaining and improving the reputation of businesses in such adverse conditions. This study explores the PR strategies applied by Crystal Hotel to enhance its reputation in the highly competitive South Jakarta market. The study utilized qualitative methods, including interviews and observations, focusing on key informants such as the hotel's Public Relations team, front office management, and loyal guests. The results highlight the significance of implementing a SWOT analysis and using the POAC framework (Planning, Organizing, Actuating, Controlling) to guide the hotel's public relations activities. This approach has contributed to the hotel's increased visibility and customer loyalty, ultimately improving its reputation.